CHARACTER EDUCATION BASED ON LOCAL WISDOM SIRI™ NA PACCE IN SOCIOLOGY LEARNING - Rahmi, Nurazizah; Ruyadi, Yadi; Wilodati, Wilodati (Universitas Negeri Medan, 2023)
Technological developments have opened up the opportunity for every mixed culture, with negative and positive effects. One negative impact is that students tend to imitate foreign cultures and forget their culture's local wisdom values. Thus, the study intended to see the concept of integrating character education in siri™ na pacce™s local wisdom through sociology. This type of research is a library study that uses books and other literature as primary objects. Studies show how integrating siri™ na pacce™s value in sociology can be done through four strategies. First, exemplary strategy. The teacher, as the subject, gives an example of any action, behavior, or words that indicate siri™ na pacce's attitude. The second strategy is to intervene by integrating values-based character education siri™ na pacce in sociological studies. The third strategy is consistent breeding. After an exemplary and intervention strategy has been implemented, a strategy is needed to keep what has been implanted into a habit or habit. The fourth strategy is reinforcement. The strategy is basically done along with the breeding strategy. This integration can be an attempt to introduce and pass on local culture to the student, as well as good character creation.